Trastuzumab Emtansine (T-DM1) in Patients With HER2-Positive Metastatic Breast Cancer Previously Treated With Chemotherapy and 2 or More HER2-Targeted Agents. Issue 5 (September 2015) - Yardley, Denise A.; Krop, Ian E.; LoRusso, Patricia M.; Mayer, Musa; Barnett, Brian; Yoo, Bongin; Perez, Edith A.
<x xml:space="preserve">Abstract</x> Purpose The antibody-drug conjugate trastuzumab emtansine (T-DM1) has improved outcomes in patients with human epidermal growth factor receptor 2 (HER2)–positive metastatic breast cancer (MBC), as demonstrated in phase III studies. Few data approximating its use in routine clinical practice are available. Methods The T-DM1 Patient Access Study was an expanded-access, multicenter study of T-DM1 in US patients with pretreated HER2–positive locally advanced breast cancer or MBC. The primary endpoint was safety. The secondary endpoint was investigator-assessed objective response rate among patients with measurable disease at baseline. Data are presented for the first 215 enrolled patients. Results The median number of prior systemic MBC agents was 8 (range, 3–23). At baseline, median left ventricular ejection fraction was 60%, and 52.6% of patients had nonclinically significant cardiovascular disease. Median T-DM1 treatment duration was 5.0 months (range, 0–29 months; median follow-up, 5.9 months), with 18.6% having received more than 18 cycles. The most common any-grade adverse events were fatigue (50.7%) and nausea (38.1%). Adverse events of grade 3 or greater were reported in 46.5%, most commonly thrombocytopenia and platelet count decrease (10.2%). Bleeding of grade 3 or greater was reported in 4 patients (1.9%). Cardiac dysfunction (primarily asymptomatic left ventricular ejection fraction decreases) was reported in 14 patients (6.5%). Among those with measurable disease at baseline (n = 172), objective response rate was 25.6% (95% confidence interval, 19.2%–32.8%). Discussion The safety profile of T-DM1 in this real-world setting of heterogeneous, HER2–positive, pretreated, locally advanced breast cancer or MBC was comparable with that reported in phases II and III studies of similar patient populations. T-DM1 was efficacious with no new safety signals.